2009
DOI: 10.1111/j.1365-2559.2009.03458.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endocan (ESM‐1) is markedly overexpressed in clear cell renal cell carcinoma

Abstract: Our results showed that endocan is overexpressed in patients with RCC. Endocan could therefore appear as a marker of interest in the follow-up and may be a potential parameter to monitor the tumour response to anti-angiogenic therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 31 publications
9
90
0
Order By: Relevance
“…Endocan is a secreted proteoglycan (12) that is upregulated by growth factors and chemokines in vitro (13,14) and on tumor vasculature in several types of cancer (15)(16)(17), with diverse suggested biologic roles (18). Using quantitative reverse-transcription PCR (qRT-PCR) and immunohistochemistry, we found that endocan was strongly upregulated on tumor vascular endothelium and that its expression correlated with the invasiveness of bladder cancer.…”
Section: Introductionmentioning
confidence: 95%
“…Endocan is a secreted proteoglycan (12) that is upregulated by growth factors and chemokines in vitro (13,14) and on tumor vasculature in several types of cancer (15)(16)(17), with diverse suggested biologic roles (18). Using quantitative reverse-transcription PCR (qRT-PCR) and immunohistochemistry, we found that endocan was strongly upregulated on tumor vascular endothelium and that its expression correlated with the invasiveness of bladder cancer.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, in the clear cell renal carcinoma patients (n = 14), endocan levels were significantly higher in pT3-4 tumor stages (n = 8, median value 6.9 ng/ml) than in pT1-2 stages (n = 6, median value 2.0 ng/ ml). However, no significant difference was observed between low (n = 4) and high grade (n = 10) tumors, that could be due of size of the cohort (Leroy et al, 2010).…”
Section: Quantifying Blood Levels Of Endocanmentioning
confidence: 78%
“…The potential of endocan as a prognostic biomarker was also highlighted in a recent study with circulating endocan levels from 3-to 10-fold higher in the sera of clear cell renal carcinoma patients compared to sera from papillary carcinoma patients or from healthy volunteers (Leroy et al, 2010). Moreover, in the clear cell renal carcinoma patients (n = 14), endocan levels were significantly higher in pT3-4 tumor stages (n = 8, median value 6.9 ng/ml) than in pT1-2 stages (n = 6, median value 2.0 ng/ ml).…”
Section: Quantifying Blood Levels Of Endocanmentioning
confidence: 92%
See 1 more Smart Citation
“…IdoA is an important component of the functional structure of endocan. In cancer patients, patients with sepsis and tissue samples of healthy volunteers, serum protein endocan is present in the form of a polysaccharide (1)(2)(3)(4). Studies of the HUVEC vascular endothelial cell model show that the endocan expression level is extremely low, which cannot meet the requirements of scientific research (4).…”
Section: Introductionmentioning
confidence: 99%